Continuous DNA replication is required for late gene transcription and maintenance of replication compartments in gammaherpesviruses. - Dajiang Li; Wenmin Fu; Sankar Swaminathan (PLoS Pathogens)
Late gene transcription in herpesviruses is dependent on viral DNA replication in cis but the mechanistic basis for this linkage remains unknown. DNA replication results in demethylated DNA, topological changes, removal of proteins and recruitment of proteins to promoters. One or more of these effects of DNA replication may facilitate late gene transcription. Using 5-azacytidine to promote demethylation of DNA, we demonstrate that late gene transcription cannot be rescued by DNA demethylation. Late gene transcription precedes significant increases in DNA copy number, indicating that increased template numbers also do not contribute to the linkage between replication and late gene transcription. By using serial, timed blockade of DNA replication and measurement of late gene mRNA accumulation, we demonstrate that late gene transcription requires ongoing DNA replication. Consistent with these findings, blocking DNA replication led to dissolution of DNA replication complexes which also contain RNA polymerase II and BGLF4, an EBV protein required for transcription of several late genes. These data indicate that ongoing DNA replication maintains integrity of a replication-transcription complex which is required for recruitment and retention of factors necessary for late gene transcription.